Absence of TRPC1 Ca2+-permeable Channel Causes Placental and Fetal Growth Restriction in Mice. (7th June 2021) - Claycombe-Larson, Kate; Bundy, Amy; Roemmich, James; Singh, Brij
Abstract: Objectives: Placental tissue intracellular calcium (Ca2+) regulates placental development and growth (e.g., blastocyst development through branching morphogenesis). Maternal high-fat (HF) diet results in placental lipid accumulation, increase in inflammation, reduction in nutrient transport expression and intra uterine growth restriction (IUGR). Currently, whether maternal HF diet affects placental and fetal growth and development differentially under reduction in Ca2 + influx is not known. Thus, we hypothesized that maternal HF diet feeding decreases placental growth and development resulting in IUGR. We further hypothesized that reduction of Ca2 + influx in placenta worsens the maternal HF-induced placental dysfunction. Methods: Two-month old female B6129SF2/J wild type (WT) and transient receptor potential canonical 1 (TRPC1) protein deficient (KO) mice were fed normal fat (NF, 16% fat) and high fat (HF, 45%) diets for 12 weeks. Fetuses and placentae were examined at mid- (D12) and late- (D19) gestation. Results: Placental length, width, and weight as well as fetal weight were decreased in the TRPC1KO mice at D12 and D19 compared to that of WT mice. Expression of placental growth factor (PLGF) mRNA was decreased at D12 in TRPC1 KO mice while vascular endothelial growth factor (VEGF) mRNA levels were increased at D19 compared to WT mice. Conclusions: These findings suggest that genotypic differences rather than maternal HF diet alter placental size and weight as well as fetal weight. Decreased in PLGF mRNA may be responsible for the placental and fetal growth restriction while increase in VEGF mRNA indicates compensatory adaptation to decreased PLGF-associated placental and fetal growth restriction. Future studies are needed to determine the signaling mechanism underlying Ca2 + influx reduction- induced placental dysfunction and IUGR. Funding Sources: USDA Agricultural Research Service Project #3062–51, 000-054–00D.